2022
DOI: 10.3390/cells11233799
|View full text |Cite
|
Sign up to set email alerts
|

Replicative Senescence-Associated LINE1 Methylation and LINE1-Alu Expression Levels in Human Endothelial Cells

Abstract: One of the main challenges of current research on aging is to identify the complex epigenetic mechanisms involved in the acquisition of the cellular senescent phenotype. Despite some evidence suggested that epigenetic changes of DNA repetitive elements, including transposable elements (TE) sequences, are associated with replicative senescence of fibroblasts, data on different types of cells are scarce. We previously analysed genome-wide DNA methylation of young and replicative senescent human endothelial cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Human LINE-1 elements are seen in many cancers and the most active L1 elements have been shown to evade somatic repression 42 . APOBEC3 has been shown to repress LINEs and restrict replication 43 ; L1ME3A is differentially regulated in young versus senescent human umbilical vein endothelial cells (HUVECs) 44 and was repressed in post-flight samples. Genetic and epigenetic changes and immune responses elicited by retrotransposon reactivation have been linked to aging 35 and cancer 44 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human LINE-1 elements are seen in many cancers and the most active L1 elements have been shown to evade somatic repression 42 . APOBEC3 has been shown to repress LINEs and restrict replication 43 ; L1ME3A is differentially regulated in young versus senescent human umbilical vein endothelial cells (HUVECs) 44 and was repressed in post-flight samples. Genetic and epigenetic changes and immune responses elicited by retrotransposon reactivation have been linked to aging 35 and cancer 44 .…”
Section: Discussionmentioning
confidence: 99%
“…APOBEC3 has been shown to repress LINEs and restrict replication 43 ; L1ME3A is differentially regulated in young versus senescent human umbilical vein endothelial cells (HUVECs) 44 and was repressed in post-flight samples. Genetic and epigenetic changes and immune responses elicited by retrotransposon reactivation have been linked to aging 35 and cancer 44 . Data from the NASA Twins study showed that APOBEC3A was up-regulated in lymphocyte-depleted cells as time in space increased 26 .…”
Section: Discussionmentioning
confidence: 99%
“…One mechanism leading to the accumulation of cytoplasmic dsRNA and RNA:DNA hybrids during cellular senescence is related to the relocalization of sirtuins to areas of DNA double-strand break, causing the loss of heterochromatin structure and ultimately leading to the transcription of retrotransposable elements [ 31 ]. In this regard, we previously demonstrated a higher abundance of the RNA and complementary DNA sequences of two among the major retrotransposable elements, i.e., Alu and LINE1, in senescent ECs [ 32 ]. The increased presence of cytoplasmic RNA:DNA hybrids in senescent and HG-treated ECs corroborates our previous observation of reduced expression of RNase H2, the enzyme that specifically degrades the RNA moiety of RNA:DNA hybrids [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation is an epigenetic mechanism that is regulated by a combination of methyltransferases and demethylases, and a central role for DNA methylation in vascular senescence-related diseases has been identified [ 60 ]. Ramini et al analyzed genome-wide DNA methylation in normal and senescent HUVECs and noted a significant increase in demethylated sequences in senescent cells [ 61 ]. Zhang et al reported that homocysteine promotes EC senescence by promoting hTERT promoter demethylation and downregulating hTERT expression in mouse aortic ECs [ 62 ].…”
Section: Molecular Mechanisms Of Ec Senescencementioning
confidence: 99%